2022
DOI: 10.3390/jpm12050726
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Preoperative Lymph Node Staging in Patients with Muscle-Invasive Bladder Cancer Using Radiomics on Computed Tomography

Abstract: Approximately 25% of the patients with muscle-invasive bladder cancer (MIBC) who are clinically node negative have occult lymph node metastases at radical cystectomy (RC) and pelvic lymph node dissection. The aim of this study was to evaluate preoperative CT-based radiomics to differentiate between pN+ and pN0 disease in patients with clinical stage cT2-T4aN0-N1M0 MIBC. Patients with cT2-T4aN0-N1M0 MIBC, of whom preoperative CT scans and pathology reports were available, were included from the prospective, mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…In fact, to characterize preoperatively the N status with more precision would help not only CC patients but also several other oncologic districts. For instance, an interesting study conducted on bladder cancer by Starmans M P A et al [26] showed how radiomics showed no improvement in the discrimination between N0 and N+. Among the possible explanations found by the authors, there is a bias in the N+ feature characteristics that also includes benign lymph nodes due to the lack of direct labelling on the pathology, and then there is the possibility of missing pathologic lymph nodes measuring less than 3 mm due to the intrinsic limits of the CT slice thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, to characterize preoperatively the N status with more precision would help not only CC patients but also several other oncologic districts. For instance, an interesting study conducted on bladder cancer by Starmans M P A et al [26] showed how radiomics showed no improvement in the discrimination between N0 and N+. Among the possible explanations found by the authors, there is a bias in the N+ feature characteristics that also includes benign lymph nodes due to the lack of direct labelling on the pathology, and then there is the possibility of missing pathologic lymph nodes measuring less than 3 mm due to the intrinsic limits of the CT slice thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Starmans et al extracted 564 radiomics features after manual segmentation of lymph nodes in 209 patients with clinically T2-T4aN0-N1M0 muscle-invasive bladder cancer, of whom preoperative CT scans and pathology reports were available [ 7 ]. Among the included patients, 50 patients were pathologically proven node-negative at radical cystectomy.…”
Section: Discussionmentioning
confidence: 99%